The larva of Rhyacophila albardana McLachlan 1879, including a discriminatory matrix to the Rhyacophila larvae with comb-shaped gills of Austria, Germany and Switzerland (Rhyacophilidae, Trichoptera) - Weinzierl, Armin; Malicky, Hans; Waringer, Johann (Zootaxa, 2021)
Final instar larvae collected in the Rißbach (Isar catchment, Bavaria) were positively associated with adults of Rhyacophila albardana by barcoding; final instar larvae and adults of this species also were collected at the same time and site in the Lech River (Austria) in the absence of confusing species. These collections and associations enabled a description of the hitherto unknown larva of this species. We present information on the morphology of the larva and illustrate the most important diagnostic features. This dataset is included in a discriminatory matrix of the other larvae with comb-shaped gills (Rhyacophila Hyperrhyacophila Group) known so far from Austria, Germany, and Switzerland. Species can be separated by coloration patterns of the head and prosternum morphology. Rhyacophila albardana is known from Austria, France, Germany, Italy, and Switzerland (Neu et al. 2018).